TINGKAT KEPUASAN PASIEN TERHADAP PELAYANAN OBAT ANTIHIPERTENSI PADA PASIEN RAWAT JALAN DI RS X PEKANBARU - Muhajri Agusfina; Renatalia fika; Ainun Naim; Mevy Trisna; Ahmad Asrawi (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2025)
Abstract: Pharmacy personnel play a role in providing accurate, clear and up-to-date information to patients. Providing drug information to patients is important so that patients receive the right and proper treatment. This study aims to determine the level of patient satisfaction with drug services for outpatients at X Hospital. This study is an observational/survey study with a descriptive research design. Based on the results of the study conducted on the level of public satisfaction with drug services by pharmacy personnel at X Hospital, Pekanbaru, the level of satisfaction was obtained in the Satisfied category (67%). This result is an average of 5 dimensions of satisfaction, namely reliability 59% in the quite satisfied category, responsiveness 70% in the satisfied category, attention (empathy) 68% in the very satisfied category, assurance 69% in the satisfied category, tangible facilities 69% in the satisfied category. The level of patient satisfaction with drug services at X Hospital from the five dimensions of satisfaction does not have a very satisfied category.